2007
DOI: 10.1111/j.1442-9071.2007.01451.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the rebound tonometer with the Goldmann applanation tonometer in glaucoma patients

Abstract: The RBT slightly overestimated the IOP value by 0.43 mmHg on average when compared with the GAT. Nevertheless, the RBT readings appeared to be more affected by the various thicknesses of different corneas when compared with those obtained using the GAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 13 publications
3
41
1
4
Order By: Relevance
“…In eight studies 106,145,154,165,190,[209][210][211] (57%), individual measures taken within 1 hour were reported and the same clinical data were available for interpretation as would be in clinical practice. Ten studies 106,107,145,154,165,167,184,207,209,211 (71%) reported whether or not the examiner(s) were masked to the results. In seven studies 106,107,145,165,207,209,211 (50%), the tonometers used were calibrated.…”
Section: Rebound Tomometermentioning
confidence: 99%
See 4 more Smart Citations
“…In eight studies 106,145,154,165,190,[209][210][211] (57%), individual measures taken within 1 hour were reported and the same clinical data were available for interpretation as would be in clinical practice. Ten studies 106,107,145,154,165,167,184,207,209,211 (71%) reported whether or not the examiner(s) were masked to the results. In seven studies 106,107,145,165,207,209,211 (50%), the tonometers used were calibrated.…”
Section: Rebound Tomometermentioning
confidence: 99%
“…Seven studies 160,167,184,207,[209][210][211] reported on acceptability and/or practicality for RT. The data are shown in Appendix 6.…”
Section: Acceptability and Practicalitymentioning
confidence: 99%
See 3 more Smart Citations